City integration and tourism development in the Greater Bay Area, China - Luo, Jian Ming; Lam, Chi Fung (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"City Integration and Tourism Development in the Greater Bay Area, China explores the tourism development related issues of city integration in the Greater Bay Area. This book starts with a general introduction to the background of the Greater Bay Area in China. Chapter 2 is a historical review, focusing on tourism development in GBA. Chapter 3 introduces the concept of city integration and the profile of GBA. Chapter 4 discusses the effect of city integration on tourism development. Chapter 5 describes the trends of city integration and tourism. Lastly, Chapter 6 is a case study with recommendations for city destination management. This book is a valuable resource for social science researchers and those in related fields, such as city planners and tourism officers. This book is recommend reading for advanced undergraduate or postgraduate students of urban tourism, tourism economics, and tourism management"--
OCLC-licensed vendor bibliographic record.
Keywords: City planning -- China -- Guangdong Sheng; City planning -- China -- Hong Kong; City planning -- China -- Macau (Special Administrative Region); Regional planning -- China -- Guangdong Sheng; Regional planning -- China -- Hong Kong; Regional planning -- China -- Macau (Special Administrative Region); Tourism -- China -- Guangdong Sheng -- Planning; Tourism -- China -- Hong Kong -- Planning; Tourism -- China -- Macau (Special Administrative Region) -- Planning; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism